The Role of Pinch Analysis for Industrial ORC Integration. (September 2017) - Olsen, Donald; Abdelouadoud, Yasmina; Liem, Peter; Wellig, Beat
Abstract: In many industrial companies a significant proportion of their total energy use is for process heat resulting in the need for improving thermal energy efficiency. A common technique to improve efficiency is through process heat recovery. Pinch analysis is a key method for optimizing industrial heat recovery resulting in greater energy efficiency and profitability. The method also shows how energy conversion units such as heat pumps, combined heat and power systems or organic Rankine cycles (ORC) can be optimally integrated into a process. An ORC converts low temperature waste heat (e.g. 100-200°C) into electricity. However, the integration of an ORC requires a sound conceptual design to ensure proper integration. In this paper the importance and application of pinch analysis for integrating an ORC is presented. Pinch analysis plays a significant role in the development of a sound conceptual design as it identifies and quantifies the amount of waste heat as well as allows the determination of the streams most suitable for the ORC. The so called grand composite curve is used for the integration of an ORC to ensure the proper placement when considering the entire process. A properly integrated ORC that uses waste heat as a heat source must operate below the pinch point, i.e. the ORC takes heat from below the pinch point and converts a part of it to electricity and rejects the remaining heat to the environment. This methodology stresses improving the overall process energetic efficiency first through heat recovery before using (real) waste heat in an ORC. A novel industrial case study is presented to illustrate proper ORC integration showing the benefit energetically but limited financially under the given process and economic conditions.